ChemInform Abstract: Room Temperature Copper‐Catalyzed Oxidative Amidation of Terminal Alkynes for the Synthesis of α‐Ketoamides Using O‐Benzoyl Hydroxylamines as Aminating Reagent and Oxidant. Issue 52 (6th December 2016) - Shen, Guodong; zhao, Lingyu; Wang, Yichen; Zhang, Tongxin
Abstract: The title reaction only applies to terminal aryl alkynes and tertiary amines.